The Ability to Utilize Cohesive Devices in Report Texts Written by English Department Students - Ni Kadek Chandra Pithaloka; I Gusti Agung Sri Rwa Jayantini (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
This qualitative research investigates the utilization of cohesive devices in report writing among English Department students. The study delves into the application of grammatical and lexical cohesive devices in the students' report writing that is connected to the students’ ability in promoting the cultural values they have to report. The research employed a comprehensive approach, including the observation on the students’ field study and interview, as well as content analysis to gain deeper contextual insights into language usage and the contribution of authentic activities prior to report writing on environmental and cultural issues. The findings demonstrate the most frequently used devices are